Uma proposta de solução para funcionamento offline em aplicações android - Guedes, Jean Guerethes Fernandes (2015)
Given the growing demand for the development of mobile applications, driven by use increasingly common in smartphones and tablets grew in society the need for remote data access in full in the use of mobile application without connectivity environments where there is no provision network access at all times. Given this reality, this work proposes a framework that present main functions are the provision of a persistence mechanism, replication and data synchronization, contemplating the creation, deletion, update and display persisted or requested data, even though the mobile device without connectivity with the network. From the point of view of the architecture and programming practices, it reflected in defining strategies for the main functions of the framework are met. Through a controlled study was to validate the solution proposal, being found as the gains in reducing the number of lines code and the amount of time required to perform the development of an application without there being significant increase for the operations.